Numerical Method for Solving Iterative Partial Differential Equations - Podisuk, Maitree; Suchatvejpoom, Suntorn; Chaichuay, Chinda (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this paper, we introduced the Newton Divided Difference Method and Backward Difference Approximation to solve iterative partial differential equations in the case of the existing numerical methods can not be used. Keywords: - E-mail: cast@kmitl.ac.th